Pendampingan Pemberdayaan UKS dan Kebersihan Kamar Mandi SDN 01 Ketindan Lawang Jawa Timur - Wulandari, Mayang; Khiong, Tjhia Khie; Ristanto, Riki; Mahadini, Chantika (Journal of Health Innovation and Community Services, 2023)
SDN 01 Ketindan already has a UKS but it has been abandoned due to the pandemic. The UKS temporarily functions as a storage area only. In addition, SDN 01 Ketindan has several dirty smelling bathrooms with several broken doors so students cannot use them. The purpose of this community service activity is to increase the knowledge and skills of partners (SDN 01 Ketindan students) regarding the function of the UKS for health services and overcoming minor injuries experienced by students or teachers. take a clean bath and cultivate the habit of keeping the bathroom clean to stay healthy. This community service was carried out through counseling methods about bathroom cleanliness and the importance of UKS. Apart from that, infrastructure repairs were carried out in this case the bathrooms by replacing all the doors, cleaning the floors, repairing leaking bathtubs, and repainting the walls. This community service has been carried out by educating school residents about UKS knowledge and bathroom cleanliness as well as products in the form of repairs to all bathrooms as a means of supporting teaching and learning activities. This activity is still ongoing because UKS infrastructure and training for UKS officers have not been carried out due to funds still being allocated for bathroom repairs.